APPLICATION OF WEB-BASED SHORT COURSE SEMESTER - Teguh Santoso; Ir.Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2003)
Taking courses in a timely manner is a proud and coveted for students, let alone be able to run faster. This can be performed if there are facilities and support between the parties, both the support of human resources and supporting resources, namely the information technology resources affection if not utilized.From these resources, we need to optimize technology resources as a means of support. Means of support that includes hardware and software support facilities, so the integration between them and backed by human resources will create a data application that helps take a decision.It provides an adequate facility to support the development of this application, because a good means of support would facilitate the use and development of this application.Accessing information through the Internet is considered faster and easier than traditional systems / manuals, though in some ways still needed the system manually to specific purposes.